Pengaruh Green Accounting, Environmental Performance, dan Material Flow Cost Accounting (MFCA) Terhadap Sustainable Development - Helfiani Putri; Lilik Handajani; Indria Puspitasari Lenap (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2024)
Sustainable development is a concept that focuses on optimizing the use of resources and protecting the environmental and social aspects both now and in the future. The environmental crisis is an important issue today with many cases of environmental damage and pollution occurring as a result of company activities. This study aims to examine the effect of green accounting, environmental performance and material flow cost accounting on sustainable development. This research is an associative research and uses a quantitative approach. The secondary data used is obtained from annual reports and sustainability reports. The population in this study are manufacturing companies sector consumer goods industry listed in the Indonesia Stock Exchange during the period 2018-2022 by using purposive sampling method, which obtained a sample of 29 companies. Data were analyzed using panel data regression with E-Views 10 software. This research shows the results that the green accounting variable has a negative and insignificant effect on sustainable development, the environmental performance variable has a positive and insignificant effect on sustainable development and the material flow cost accounting variable has a positive and significant effect on sustainable development.